Analysis of the Effect of Abnormal Tissue Size on the S11 Response of a Monopole Antenna Using a Realistic Heterogeneous Breast Phantom - Isma Hanifah; Irmayatul Hikmah; Nur Afifah Zen; Muntaqo Alfin Amanaf (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2026)
Breast cancer remains one of the leading causes of death among women. Although conventional diagnostic methods are available, they are limited by radiation exposure risks, high operational costs, and limited accessibility. Alternatively, microwave technology offers the advantage of using non-ionizing radiation and leveraging differences in dielectric properties between healthy and abnormal tissues. The development of this technology, however, requires experimental validation using phantoms capable of realistically and stably representing the dielectric characteristics of biological tissues. In this study, a heterogeneous breast phantom was developed to evaluate antenna sensitivity in detecting variations in the size of abnormal tissue through S11 parameter analysis. The contribution of this study is the fabrication of a four-layer phantom (skin, fat, glandular, and abnormal tissue) using agar–gelatin materials. Sodium benzoate was added as a preservative to prevent microbial growth, and NaCl was incorporated to adjust the conductivity, enabling dielectric properties closer to those of real breast tissue. In the testing phase, two variations of abnormal tissue with diameters of 4 cm and 6 cm were inserted into the glandular layer to simulate different pathological conditions. The S11 response was measured using a vector network analyzer (VNA) over the 2–6 GHz frequency range with a monopole antenna placed 1 cm from the phantom. The results showed that the antenna sensor could detect differences between normal phantoms and phantoms with anomalies, particularly in the 2.5–3 GHz range. The normal phantom showed the lowest resonant frequency at 2.51 GHz with a return loss of −36.35 dB. In contrast, phantoms with 4 cm and 6 cm abnormal tissues showed shifts to 2.52 GHz (−29.71 dB) and 2.53 GHz (−28.69 dB), respectively. A maximum return loss difference of approximately 7.66 dB was observed, indicating high sensitivity to internal structural changes. These significant differences in return loss values indicate that the developed system is highly sensitive to changes in internal structure. This combination of a heterogeneous phantom and an antenna sensor has the potential to serve as a simple experimental platform to support breast cancer detection technology.